2015
DOI: 10.1111/obr.12258
|View full text |Cite
|
Sign up to set email alerts
|

Appetite and body weight regulation after bariatric surgery

Abstract: Bariatric surgery continues to be remarkably efficient in treating obesity and T2DM and a debate has started whether it should remain the last resort only or also be used for the prevention of metabolic diseases. Intense research efforts in humans and rodent models are underway to identify the critical mechanisms underlying the beneficial effects with a view towards non-surgical treatment options. This non-systematic review summarizes and interprets some of this literature, with an emphasis on changes in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 154 publications
(220 reference statements)
2
72
0
2
Order By: Relevance
“…Lastly, the effects of bariatric surgery also act at a behavioral level, decreasing hunger, increasing satiety, and reducing overall caloric intake following surgery [67,68]. In RYGB and VSG, studies report reductions in certain eating behaviors including food cravings/hunger, emotional eating and uncontrolled eating with one notable exception: no study has found significant change in cognitive restraint [69][70][71][72].…”
Section: Potential Mechanisms Leading To Weight Loss and Improved Diamentioning
confidence: 95%
“…Lastly, the effects of bariatric surgery also act at a behavioral level, decreasing hunger, increasing satiety, and reducing overall caloric intake following surgery [67,68]. In RYGB and VSG, studies report reductions in certain eating behaviors including food cravings/hunger, emotional eating and uncontrolled eating with one notable exception: no study has found significant change in cognitive restraint [69][70][71][72].…”
Section: Potential Mechanisms Leading To Weight Loss and Improved Diamentioning
confidence: 95%
“…Despite some contention 714 (Werling et al, 2013(Werling et al, , 2015, changes in energy expenditure or the rate by which nutrients are taken up from the intestine do not explain the initial efficacy or the sustained weight reduction (Olbers et al, 2006;Odstrcil et al, 2010;Carswell et al, 2014;Münzberg et al, 2015;Schmidt et al, 2016). Chronic changes in food consumption are typically reported after bariatric surgery and are considered a causal factor in sustained weight loss (Brolin et al, 1994;Sjöström et al, 2004;Laurenius et al, 2012;Münzberg et al, 2015).…”
Section: Bariatric Surgery: a Benchmark For Efficacymentioning
confidence: 99%
“…Despite some contention 714 (Werling et al, 2013(Werling et al, , 2015, changes in energy expenditure or the rate by which nutrients are taken up from the intestine do not explain the initial efficacy or the sustained weight reduction (Olbers et al, 2006;Odstrcil et al, 2010;Carswell et al, 2014;Münzberg et al, 2015;Schmidt et al, 2016). Chronic changes in food consumption are typically reported after bariatric surgery and are considered a causal factor in sustained weight loss (Brolin et al, 1994;Sjöström et al, 2004;Laurenius et al, 2012;Münzberg et al, 2015). Molecular mechanisms that support reduction in food intake seem, however, not to rely on physical limitations of the gastrointestinal tract (Ryan et al, 2014), but instead pertain to changes in food preference, taste perception, and alterations in the food reward system (Scruggs et al, 1994;Burge et al, 1995;Miras and le Roux, 2010;Shin and Berthoud, 2011;Mathes and Spector, 2012;Laurenius et al, 2013).…”
Section: Bariatric Surgery: a Benchmark For Efficacymentioning
confidence: 99%
“…The immediate caloric decrease after bariatric surgery is caused by a substantial reduction in hunger and an increase in satiation (10). The role of anatomical restrictions of the ventricle and nonmechanical factors, such as gut hormones, bile acids, and gut microbiota, remain under investigation (11)(12)(13). However, little is known about the associations between changes in total energy intake and energy-contributing nutrients (i.e., the macronutrients carbohydrates, fat, and protein) and the long-term weight change in patients who have undergone bariatric surgery (14).…”
Section: Introductionmentioning
confidence: 99%